Residents' preferred policy actions for shrinking cities. (3rd May 2016) - Guimarães, Maria Helena; Nunes, Luis Catela; Barreira, Ana Paula; Panagopoulos, Thomas
ABSTRACT: Cities facing a continued and prolonged process of population decline require innovative urban regeneration policies complementary to growth-oriented policies. Losing inhabitants involves a decrease in economic activity and social capital. Therefore citizens' participation in defining policies to cope with population decline is being increasingly advocated. This research focused on four shrinking cities of Portugal to capture residents' knowledge about the strengths and weaknesses of their city of residence as well as the policies and actions they prioritized for dealing with the population decline. The responses from 701 questionnaires show that economic revival policies as well as safety and accessibility policies were preferred. To put these policies into action, the recovery of industrial activity, the creation of business incubators, an improvement in law enforcement, and public lighting were ranked as top priorities. Rank-ordered logistic regression models were used to understand which variables influenced the residents' rankings. We found that the evaluation of the city's characteristics impact the ranking of the policies and actions. Hence, residents show a high level of coherence when engaging in a discussion at the level of policy-making. Therefore, the findings support residents' involvement in decision-making processes regarding urban regeneration in shrinking cities.